High Level of Uric Acid Promotes Atherosclerosis by Targeting NRF2-Mediated Autophagy Dysfunction and Ferroptosis. (18th April 2022) - Yu, Wei; Liu, Weidong; Xie, De; Wang, Qiang; Xu, Chenxi; Zhao, Hairong; Lv, Jiaming; He, Furong; Chen, Bingyang; Yamamoto, Tetsuya; Koyama, Hidenori; Cheng, Jidong
Abstract : Atherosclerotic vascular disease (ASVD) is the leading cause of death worldwide. Hyperuricemia is the fourth risk factor for atherosclerosis after hypertension, diabetes, and hyperlipidemia. The mechanism of hyperuricemia affecting the occurrence and development of atherosclerosis has not been fully elucidated. Mononuclear macrophages play critical roles in all stages of atherosclerosis. Studies have confirmed that both hyperuricemia and ferroptosis promote atherosclerosis, but whether high level of uric acid (HUA) promotes atherosclerosis by regulating ferroptosis in macrophages remains unclear. We found that HUA significantly promoted the development of atherosclerotic plaque and downregulated the protein level of the NRF2/SLC7A11/GPX4 signaling pathway in ApoE −/− mice. Next, we evaluated the effect of HUA and ferroptosis inhibitor ferrostatin-1 (Fer-1) treatment on the formation of macrophage-derived foam cells. HUA promoted the formation of foam cells, decreased cell viability, and increased iron accumulation and lipid peroxidation in macrophages treated with oxidized low-density lipoprotein (oxLDL); these effects were reversed by Fer-1 treatment. Mechanistically, HUA significantly inhibited autophagy and the protein level of the NRF2/SLC7A11/GPX4 signaling pathway. Fer-1 activated autophagy and upregulated the level of ferroptosis-associated proteins. Moreover, an NRF2 inducer (tertbutyl hydroquinone (TBHQ)) and autophagy activator (rapamycin (RAPA)) could reverse the inhibitory effect of HUA on foam cell survival. Our results suggest that HUA-induced ferroptosis of macrophages is involved in the formation of atherosclerotic plaques. More importantly, enhancing autophagy and inhibiting ferroptosis by activating NRF2 may alleviate HUA-induced atherosclerosis. These findings might contribute to a deeper understanding of the role of HUA in the pathogenesis of atherosclerosis and provide a therapeutic target for ASVD associated with hyperuricemia.